2013
DOI: 10.4103/0019-5154.117308
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma, oculo-cutaneous albinism and actinic keratosis in a native Indian

Abstract: The report highlights the occurrence of basal cell carcinoma in a native Indian with oculo-cutaneous albinism, an association not frequently encountered. The clinical and histopathological features, which assisted to form the diagnosis, are outlined. A high degree of suspicion and timely recognition of the potentially aggressive neoplasm, under this unusual circumstance, is the key to its diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Basal cell carcinoma in albino skin is rarely reported in the Indian subcontinent and we could trace only one case report from India upon literature survey. [4] However, a study by Kiprono et al . revealed almost identical proportion of squamous cell carcinomas and basal cell carcinomas in African albinos.…”
mentioning
confidence: 99%
“…Basal cell carcinoma in albino skin is rarely reported in the Indian subcontinent and we could trace only one case report from India upon literature survey. [4] However, a study by Kiprono et al . revealed almost identical proportion of squamous cell carcinomas and basal cell carcinomas in African albinos.…”
mentioning
confidence: 99%
“…Underlying OCA is not known to alter the management of skin malignancies. This is evident from various case reports where nonmetastatic skin tumors were managed with wide local excision in patients with albinism [ 9 , 11 ]. Hence, each individual lesion was excised and submitted for histological assessment.…”
Section: Discussionmentioning
confidence: 99%
“…There are few case reports that have described the synchronous occurrence of more than one type of skin malignancy or premalignant lesion in individuals with OCA. Chatterjee et al reported the case of an Indian albino who presented with concurrent BCC and actinic keratosis, a precursor of SCC [ 9 ]. A prospective study by van der Westhuizen et al described 16 OCA patients with melanocytic or pigmented skin lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Concurrent diagnoses reported in the articles included SCC ( n = 22), malignant melanoma ( n = 9), AK ( n = 5), actinic damage ( n = 5), and one each of actinic chelitis, epidermoid carcinoma, and Merkel cell carcinoma (where n is number of articles) (Table 2). 2–8,11–39 …”
Section: Discussionmentioning
confidence: 99%